2015
DOI: 10.1371/journal.pone.0130048
|View full text |Cite
|
Sign up to set email alerts
|

C6 Peptide-Based Multiplex Phosphorescence Analysis (PHOSPHAN) for Serologic Confirmation of Lyme Borreliosis

Abstract: BackgroundA single-tier immunoassay using the C6 peptide of VlsE (C6) from Borrelia burgdorferi sensu stricto (Bb) has been proposed as a potential alternative to conventional two-tier testing for the serologic diagnosis of Lyme disease in the United States and Europe.ObjectiveTo evaluate the performance of C6 peptide based multiplex Phosphorescence Analysis (PHOSPHAN) for the serologic confirmation of Lyme borreliosis (LB) in Russian patients.MethodsSerum samples (n = 351) were collected from 146 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
4
8
0
3
Order By: Relevance
“…Detection of IgM and IgG antibodies of C6 peptides using ELISA has a sensitivity of >70% for detecting Lyme disease. Pomelova et al showed that of their 146 Lyme disease patients, 51% had seroconversion of IgM antibodies, and 88% had seroconversion of IgG antibodies [28]. Liange et al showed that in acute infected patients, including early localized and early disemminated infection) sensitivity of the C6 ELISA was 74%, In late phase disease, sensitivity was 100%.…”
Section: Diagnosismentioning
confidence: 99%
“…Detection of IgM and IgG antibodies of C6 peptides using ELISA has a sensitivity of >70% for detecting Lyme disease. Pomelova et al showed that of their 146 Lyme disease patients, 51% had seroconversion of IgM antibodies, and 88% had seroconversion of IgG antibodies [28]. Liange et al showed that in acute infected patients, including early localized and early disemminated infection) sensitivity of the C6 ELISA was 74%, In late phase disease, sensitivity was 100%.…”
Section: Diagnosismentioning
confidence: 99%
“…Для создания мультиплексного теста была применена биочип-технология ФОСФАН ТМ [16], эффективность которой для серологической диагностики ряда инфекций была продемонстрирована ранее [17]. Для решения поставленных задач в состав иммуночипа, помимо рекомбинантных белков gG1 и gG2, были включены лизатные антигены ВПГ и рекомбинантный мозаичный антиген ЦМВ.…”
Section: Abstract: Phosphan-based Multiplex Immunoassay; Hsvunclassified
“…Выполнение мультиплексного теста. ФОСФАН проводили по методикам, аналогичным описанным ранее [17]. Исследуемые образцы сыворотки крови, предварительно разведенные 1:100 в 0,01 М фосфатно-солевого буфера, рН 7,4, вносили по 100 мкл в лунки микропланшета с напечатанными антигенами и инкубировали 2 ч на шейкере при комнатной температуре.…”
Section: материал и методыunclassified
See 1 more Smart Citation
“…With the Borrelia spirochetes being found in the brains in Alzheimer's disease, [24][25][26] and with Montauk knee being a representation of Lyme arthritis, and with biofilms present in both joints and brains, all that is missing is proof of the innate immune system activity. However, increased activity of the adaptive immune system with IgG has been noted [31].…”
Section: Lyme Diseasementioning
confidence: 99%